1979
DOI: 10.1139/z79-056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of progesterone and estradiol-17β on ovarian fluid secretion in the threespine stickleback, Gasterosteus aculeatus L., form trachurus

Abstract: Immersion of postspawning sticklebacks in seawater containing 0.5 ppm progesterone for 5 days (medium changed daily) caused marked fluid accumulation in the ovarian cavity. A similar effect was obtained in overripe fish treated in the same way for 9 days; overripe fish have overripe ovulated eggs in the ovarian cavity with very little fluid. Estradiol-17β (1 ppm) also caused ovarian fluid secretion in some postspawning fish, but this may be related to its marked stimulation of ovarian recrudescence. The findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…Immersion in 17,2013-P did not produce a significant effect although a similar trend was seen. These findings support the suggestion of Lam et al (1979) that P plays a role in preventing overripening in fish. Lam et al (1979) found that P stimulated the secretion of ovarian fluid in the threespined stickleback.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Immersion in 17,2013-P did not produce a significant effect although a similar trend was seen. These findings support the suggestion of Lam et al (1979) that P plays a role in preventing overripening in fish. Lam et al (1979) found that P stimulated the secretion of ovarian fluid in the threespined stickleback.…”
Section: Discussionsupporting
confidence: 91%
“…These findings support the suggestion of Lam et al (1979) that P plays a role in preventing overripening in fish. Lam et al (1979) found that P stimulated the secretion of ovarian fluid in the threespined stickleback. On the basis of this and their earlier (Lam et al 1978) findings, they postulated that steroids secreted by POFs, particularly P, maintain the secretion of OF which in turn maintains the viability of ovulated eggs in the ovarian cavity.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations